Pengaruh Variabel Kualitas Sistem Informasi Terhadap Kepuasan Pengguna Sistem Informasi Model EUCS - Erick Sorongan; Hilmansyah Hilmansyah; Hadiyanto Hadiyanto (Ikatan Ahli Informatika Indonesia (IAII), 2019)
The application of information systems with various types of convenience offered can reflect the quality of service of an organization, the quality of service can be said to be very good if the service meets the needs and expectations of users. This kind of evaluation can be done by applying a tested model but problems arise when latent variables in the method used are not fully able to identify factors that influence user satisfaction. From the results of research using the end user satisfaction model, the R-Square value is 0.653, which means that 65.3% of user satisfaction can be found through latent variables found in the EUCS model while the remaining 34.7% can be explained through external variables. This study aims to analyze external factors outside the EUCS model, one of which is by using the information system quality variables contained in the Delone and Mclane information system success model. The way to do this is to add an external variable to the EUCS model and then analyze the outer model and analyze the structural model using the structural equation model. The results showed that the independent system quality variable has a t-statistic value of 3.445 or greater than t-table 1.96 which means that the external latent variables of the Delone and Mclean model can be used to explain the satisfaction factors (from the external variable side) of the user information system on the EUCS model.